Preventing Falls and Fall-Related Injuries at Home. Issue 1 (January 2018) - Powell-Cope, Gail; Thomason, Susan; Bulat, Tatjana; Pippins, Karla M.; Young, Heather M.
Abstract : N/A: This article is part of a series, Supporting Family Caregivers: No Longer Home Alone, published in collaboration with the AARP Public Policy Institute. Results of focus groups, conducted as part of the AARP Public Policy Institute's No Longer Home Alone video project, supported evidence that family caregivers aren't given the information they need to manage the complex care regimens of family members. This series of articles and accompanying videos aims to help nurses provide caregivers with the tools they need to manage their family member's health care at home. The articles in this new installment of the series explain principles for promoting safe mobility that nurses should reinforce with family caregivers. Each article also includes an informational tear sheet— Information for Family Caregivers —that contains links to instructional videos. To use this series, nurses should read the article first, so they understand how best to help family caregivers, and then encourage the caregivers to watch the videos and ask questions. For additional information, see Resources for Nurses .